DAMPAK EKSPOR IKAN TUNA INDONESIA KE JEPANG TERHADAP NELAYAN INDONESIA - Azmiyah, Sri Muliani; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Japan is a potential market for Indonesian fishery products, especially tuna. This is because Japan is a country that has few quality fishery products so that Japan exports from Indonesia. However, for Indonesia to export to Japan, Japan has a requirement that fishermen who catch fish must use environmentally friendly methods and tools so that production can continue to be sustainable.            In discussing the problems in this study, the author uses a qualitative method that is supported by the perspective of Liberalism and the state as the level of analysis and with the theory of cooperation to analyze the impact that is caused.               This study shows that cooperation in the export of Indonesian tuna to Japan has a positive impact on Indonesia and fish fishermen in Indonesia, the impact caused is in the form of fishery facilities such as fishing ports in the Lampa Natuna Strait where the fishermen experience changes in income and get supporting facilities such as food stalls. fishermen, cooperatives, electricity, and fuel where Pertamina provides special prices for small fishermen so as to improve the welfare of Indonesian fishermen. Keywords: Exports, Tuna, IJEPA, and Indonesian Fishermen